1083. Long-Term Prognosis of 448 Infectious Endocarditis Followed by an Endocarditis Team. (26th November 2018) - Camou, Fabrice; Greib, Carine; Machelart, Irène; Dijos, Marina; Cornolle, Claire; Barandon, Laurent; Peuchant, Olivia; Wirth, Gaetane; Issa, Nahema
Abstract: Background: The management of infective endocarditis (IE) by an expert medico-surgical team through multidisciplinary consultation meetings is now recommended. While it seems clear that it can improve the short-term prognosis of patients, long-term data are still scarce. Methods: All patients hospitalized between 2013 and 2017 in the three teaching hospitals of our center with an IE treated by the multidisciplinary team were followed prospectively at 1, 3, 6, and 12 months. The main objective was to determine the 1-year mortality of the entire cohort treated by the team. Results: During the study, 493 patients had a certain or possible IE and the outcome at 1 year was known for 448 of them (4 lost to follow-up and 41 followed for less than 1 year): 254 had native valve IE (57%) and 194 had prosthetic valve IE (43%). The median age of IE patients was 69.3 years (155 patients were over 75 years old) and 329 (73%) were men. Healthcare-associated IE (HAIE) accounted for 47% of cases. A microorganism was isolated in 92% of cases ( S. aureus = 24%), 252 patients (56%) had an embolic events and 68 (15%) had heart failure. The Charlson Median Comorbidity Index (ICC) was 5.0. Two hundred sixteen patients (48%) underwent surgery. The mortality rates at 1 month, 3 months, 6 months, and 1 year were, respectively, 14.1%, 19.0%, 23.2%, and 27.7%. The ICC at inclusion of patients who died at 1 year was 6.0 vs. 4.0 for survivors. Mortality at 1 year was significantly higher in case of HAIE (33% vs. 23%), documented S. aureus IE (39% vs. 24%), exclusive medical treatment (40% vs. 15%), and heart failure (43% vs. 25%). Conclusion: While the management of IE by an endocarditis team seems to improve the short-term prognosis of IE, 1-year mortality remains high as patients are increasingly older and have severe comorbidities. Our study confirms that early prognostic factors remain in the long term and that the prognosis is better in community-acquired IE with surgery. Disclosures: All authors: No reported disclosures.